2018
DOI: 10.1371/journal.pone.0198693
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analyses of IL1A polymorphisms and the risk of several autoimmune diseases published in databases

Abstract: BackgroundBased on published data, we aimed to quantitatively elucidate the possible genetic influence of rs17561 and rs1800587 polymorphisms of the IL1A (interleukin 1 alpha) gene in the susceptibility to several autoimmune diseases.MethodsA series of meta-analyses were carried out. After database searching, we utilized our inclusion/exclusion criteria to screen and include the eligible studies. Passociation (P value of association test), Bonferroni-corrected Passociation value; false discovery rate (FDR)-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 56 publications
(63 reference statements)
1
10
0
Order By: Relevance
“…11 The members of the IL-1 family are not only the initiators but also the amplifiers of immune and inflammatory responses. 12 Inhibiting the IL-1 signaling network has been used for the treatment of inflammatory cytokinecaused autoimmune diseases and has shown promising treatment efficacy. 13 The PELI1 mRNA level has been reported to be increased in sputum from patients with recurrent asthma and COPD.…”
Section: Discussionmentioning
confidence: 99%
“…11 The members of the IL-1 family are not only the initiators but also the amplifiers of immune and inflammatory responses. 12 Inhibiting the IL-1 signaling network has been used for the treatment of inflammatory cytokinecaused autoimmune diseases and has shown promising treatment efficacy. 13 The PELI1 mRNA level has been reported to be increased in sputum from patients with recurrent asthma and COPD.…”
Section: Discussionmentioning
confidence: 99%
“…The random-effects model was applied when I 2 > 50%, indicating the presence of heterogeneity. Otherwise, if the I 2 was less than 50%, the fixed-effects model was used [ 24 ]. The Z-test was then performed to determine the significance of the pooled ORs where P <0.05 was illustrated as statistically significant.…”
Section: Methodsmentioning
confidence: 99%
“…However, this association was not supported by other relevant studies (16). And in the meta-analysis, IL-1A rs17561 or rs1800587 polymorphism seems not to be statistically linked to the risk of SSc (17). Recently, a study demonstrated a significant association between the IL-1β (IL-1B) (+3962; rs1143634) SNP and the development of a severe ventilatory restriction in SSc patients.…”
Section: The Association Of Il-1 Family Genes and Sscmentioning
confidence: 96%